Status Mutu Air Waduk Penjalin Berdasarkan Parameter Fisika-Kimia Menggunakan Metode Storet dan Indeks Pencemaran - Handayani, Anik Maulia Tri; Samudra, Sesilia Rani; Hidayati, Nuning Vita; Sarasati, Wulandari (Fakultas Perikanan dan Ilmu Kelautan, 2023)
In the vicinity of Penjalin Reservoir there are residential areas, eateries, livestock farms, rice fields, and floating net cages. These activities have the potential to lead to a decline in water quality of Penjalin Reservoir due to the direct discharge of waste into the water body. Therefore, research on the water quality status of Penjalin Reservoir is necessary as a means of monitoring water quality in the reservoir. This research aims to determine the water quality status of Penjalin Reservoir using the Storet and the Pollution Index Methods. The research method employed is a survey method, with the selection of sampling points carried out through purposive random sampling, comprising nine stations. Water quality data are analyzed descriptively and compared to the water quality standards for lakes and similar bodies of water, as outlined in the Republic of Indonesia Government Regulation No. 22 of 2021. Subsequently, the water quality status is determined using the Storet and the Pollution Index Methods, as per the Minister of Environment Decision No. 115 of 2003. The results indicate that the water quality status of Penjalin Reservoir, when used for various purposes ranging from Class 1 to Class 3 according to the Storet Method, falls within the heavily polluted category. However, according to the Pollution Index Method, it is categorized as slightly polluted. Nevertheless, Penjalin Reservoir still meets the water quality standards when utilized for agricultural irrigation.